NEOPYLUS NAHUELBUTENSIS, NUEVO GENERO Y ESPECIE DE ENOPLIINAE DE CHILE (COLEOPTERA, CLERIDAE) - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
Neopylus nahuelbutensis, new genus and new species of Enopliinae (Coleopiera, Cleridae) is described from Southern Chile. The relationships of the genus with Pylus from the Australian región and the position of both genera in the subfamilv are discussed.